(untitled) (Estudios Gerenciales, 2017)
While much has been studied regarding the wine industry in Spain and France, little has been studied in developing countries. The aim of this work is to study the characteristics of dynamic wine firms in Chile. This paper presents qualitative research and reports six cases of wine companies, where several variables are analyzed according to Barringer, Jones and Neubaum framework. These variables include prior experience, founders’ knowledge regarding large company management, the use of strategic-planning systems and the use of new technology in the majority of its production. The results of this research could prove insightful for wine entrepreneurs looking to enhance their growth, based on greater differentiation and innovation, and not only on being competitive in pricing.